2005
DOI: 10.1161/01.str.0000173183.36331.ee
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Cerebral Autoregulation in Acute Ischemic Stroke Assessed From Spontaneous Blood Pressure Fluctuations

Abstract: Background and Purpose-This study investigates dynamic cerebral autoregulation assessed from spontaneous blood pressure (ABP) and cerebral blood flow velocity (CBFV) fluctuations and its time course in acute ischemic stroke. Methods-Forty patients admitted with acute ischemic stroke in the territory of the middle cerebral artery (MCA) were enrolled. Admission National Institutes of Health Stroke score was 6Ϯ4. Study 1 was performed within 22 (Ϯ11) hours and study 2 was performed within 134 (Ϯ25) hours of ictus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
137
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(146 citation statements)
references
References 38 publications
(36 reference statements)
5
137
2
Order By: Relevance
“…Moreover, a comparison of volunteers to medicated, ventilated patients may be misleading. This has been partially discussed previously [29]. Both Tox and Mx show rapid variations which may be caused by changes in the intensity of useful components for the assessment of autoregulation (slow waves) or fast changes in the strength of dynamic regulation (see example in Fig.…”
Section: Limitationsmentioning
confidence: 81%
“…Moreover, a comparison of volunteers to medicated, ventilated patients may be misleading. This has been partially discussed previously [29]. Both Tox and Mx show rapid variations which may be caused by changes in the intensity of useful components for the assessment of autoregulation (slow waves) or fast changes in the strength of dynamic regulation (see example in Fig.…”
Section: Limitationsmentioning
confidence: 81%
“…In 9 studies, the initial stroke severity was not reported, [25][26][27][28][29][30][31][32][33] and 8 studies failed to provide information about other clinical conditions (such as arrhythmias, diabetes mellitus, and carotid pathology) associated with impaired cerebral autoregulation. 25,30,[32][33][34][35][36][37] All studies allowed hypertensive patients to be included. In 2 studies, only information about the nonaffected hemisphere was presented because of permanent occlusion of contralateral middle cerebral artery.…”
Section: Literaturementioning
confidence: 99%
“…stroke, 30,41-44,46,47 particularly when stroke is moderate to severe, [41][42][43][44] or after follow-up. 36,41 In 5 studies, impaired autoregulation also could be demonstrated in the nonaffected hemisphere, [41][42][43][44] which was particularly the case for first-ever lacunar stroke. 46 Eames et al 42 showed that these bilateral changes are unrelated to previous antihypertensive treatment, baseline BP levels, or BP changes after stroke, age, and stroke subtype or stroke severity.…”
Section: Acute Stroke and Dynamic Autoregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Prominence of the MV is also seen in the subacute stage of ischemic stroke. 10 In clinical practice, we have noted that prominent MV may be seen ipsilateral or contralateral to infarction. Such imaging signs may provide important prognostic information to guide clinicians toward the application of tissue-rescue therapies (such as recanalization or vasodilation) to prevent stroke progression during the subacute phase.…”
mentioning
confidence: 95%